Menafsirkan Mikha 6:8 dalam Konteks Pelayanan Gereja Masehi Injili di Timor - Taneo, Rolin F. S.; de Haan, Arly E.M; Takene, Anika C (Tumou Tou, 2025)
To support all its service activities, the Evangelical Christian Church in Timor has established five ministries to become instruments for GMIT to determine programs that can touch the congregation's struggles. This is important because GMIT is struggling with many humanitarian issues such as poverty, human trafficking, problematic climate and nature and many other problems. In carrying out this task, the church must be fair and act correctly so that the entire series of services is not biased. This task is framed upon Micah 6:8. Therefore, it can be said that this article is the result of an elaboration between text interpretation and a social theological approach which shows the practical side of the biblical text used as a reference. The conclusion of this article is that it can serve as material for reflection for GMIT in carrying out all its service activities while remaining faithful to the Bible, and full of justice, faithfulness and humility.